1990
DOI: 10.1080/00288233.1990.10428457
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clovers in dry hill country 6. Subterranean and white clovers at Wairakei, New Zealand

Abstract: Nine subterranean clover cultivars and 11 white clover lines were evaluated for persistence and production, under a combination of rotational grazing or cutting, for 4 years on rolling pumice hill country. The most successful subterranean clover cultivarwas 'Tallarook' , whichfor 4 yearsproduced the most dry matter (DM) (average 700 kg DM/ha per year) and accumulated the largest soil seed reserve (1500 kg seed/ha), Soil moisture stress over the summer severely limited persistence and hence production of all wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…This cultivar was consistently cited in the national evaluation series as being the most well-adapted to dry North Island hill country environments Macfarlane et al 1990;Sheath & Macfarlane 1990a;Sheath et al 1990). In the previous two trials in the present series (Dodd et al 1995a,b), its suitability for this environment was confirmed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cultivar was consistently cited in the national evaluation series as being the most well-adapted to dry North Island hill country environments Macfarlane et al 1990;Sheath & Macfarlane 1990a;Sheath et al 1990). In the previous two trials in the present series (Dodd et al 1995a,b), its suitability for this environment was confirmed.…”
Section: Resultsmentioning
confidence: 99%
“…The objective of these trials was to evaluate the persistence of a number of subterranean clover selections in a temperate, moderate-steep hill country environment. Desirable characteristics were identified in previous experiments (Sheath & Richardson 1983;Chapman et al 1986;Macfarlane et al 1990;Sheath & Macfarlane 1990a,b;Sheath et al 1990;Williams et al 1990). The screening programme included naturalised genotypes from long-term hill pastures in New Zealand, overseas accessions, and standard Australian cultivars.…”
Section: Introductionmentioning
confidence: 98%
“…Summer production superior to HUIA (Hill 1989). Increased proportion of large roots did not ensure persistence in New Zealand dry hill country (Macfarlane et al 1990c). …”
Section: Agronomic Performancementioning
confidence: 99%
“…The prevalence of frosts with spring sowing (Macfarlane et al 1990) and a high probability of bird predation at that time, may have contributed to its demise. Future use of subterranean clover might consider the cu1tivar Tallarook, which showed better persistence and production than 'Woogenellup' and 'Mt.…”
Section: White and Subterranean Clovermentioning
confidence: 99%
“…Future use of subterranean clover might consider the cu1tivar Tallarook, which showed better persistence and production than 'Woogenellup' and 'Mt. Barker' at a near-by site (Macfarlane et al 1990). …”
Section: White and Subterranean Clovermentioning
confidence: 99%